Torrefied Biomass and Where Is the Sector Currently Standing in Terms of Research, Technology Development, and Implementation - Wild, Michael; Calderón, Cristina (Frontiers in Energy Research, 2021)
Torrefaction is a thermal conversion method of biomass to produce a high-quality solid biofuel that can be used for combustion, gasification and additional non-energy related applications. Torrefied biomass has numerous advantages above today´s standard biomass fuels like log wood, wood chips and white wood pellets. This is known and promoted for long, has been proven in numerous research and demonstration projects, however large-scale industrial proof still is only these days underway. First project implementations with name plate capacity of 100kmt/a or higher are in construction or hot commissioning. In this review, the main advantages of torrefaction are shortly described, and the latest industry developments and future opportunities for the products as well as areas of need for further R&D are presented.